1959
DOI: 10.1161/01.res.7.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cardiac Control in Exercise

Abstract: Left ventricular performance during spontaneous exercise has been continuously analyzed in terms of direct recordings of diameter, effective pressure and other parameters derived by electronic computors. The changes in left ventricular performance during treadmill exercise have been compared with a number of experimentally induced responses in the same intact unanesthetized dog on the same day. These direct comparisons revealed that experimentally-induced increased venous return, reduced peripheral resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
1

Year Published

1960
1960
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(43 citation statements)
references
References 61 publications
6
35
1
1
Order By: Relevance
“…These observations provide an interesting contrast with studies which have shown that SV does not fall with the tachycardia of exercise, even at rates faster than those in our study (6)(7)(8). The exercise response of stroke volume to tachycardia differs from the results of electrical pacing, although the EDV becomes smaller in both situations.…”
Section: )contrasting
confidence: 99%
“…These observations provide an interesting contrast with studies which have shown that SV does not fall with the tachycardia of exercise, even at rates faster than those in our study (6)(7)(8). The exercise response of stroke volume to tachycardia differs from the results of electrical pacing, although the EDV becomes smaller in both situations.…”
Section: )contrasting
confidence: 99%
“…The finding that the end-diastolic size of the heart usually does not increase and, in fact, most commonly declines (9,(27)(28)(29)(30)(31), has been used to support the view that the Frank-Starling mechanism does not play a role in the cardiac response to exercise (32). It is clear from the present study that induced tachycardia in the absence of exercise reduces ventricular dimensions to a greater extent than do similar changes in heart rate during exercise.…”
Section: Discussionsupporting
confidence: 70%
“…This is well documented by the studies of Beattie et al (1930), Manning & Peiss (1958, 1960 and Rushmer et al (1959).…”
Section: Resultssupporting
confidence: 63%